Application of cross-linked natural biological matrix in preparation of wound hemostasis and / or filling materials
Through the method of preparing the natural biological matrix, the lack of existing hemostatic materials in mechanical properties and long -term application effects are solved, and the effect of rapid hemostasis during surgery and continuous degradation and guiding tissue growth after surgery.
Patent Information
- Application Number
- CN202411186421.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-28
AI Technical Summary
In actual applications of existing hemostasis materials, in addition to hemostasis performance, the mechanical properties and long-term application effects of the materials have not been effectively considered, especially in special scenarios such as the pelvic floor, abdominal cavity and oral cavity.
The natural biological substrate is used to use specific preparation methods, including disinfection, sedimentation, lipstick, extraction and cross-linking treatment, and the degree of control is between 31.71-75.98%to ensure that the material stops bleeding in time during surgery, and is in the surgery, and is in the surgery, and is in the surgery. Continue to solve the problem of wounds and bleeding after surgery.
While ensuring the mechanical performance, the material can quickly stop bleeding, and continue to degrade after surgery to prevent wound infection and inflammation, and at the same time, it has the function of guiding tissue growth.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of surgical supplies materials, and more specifically, to the application of a cross-linked natural biological matrix in the preparation of wound hemostasis and / or filling materials. Background Art
[0002] Using implant materials to guide tissue regeneration is one of the current trends in surgical repair. In surgical operations, bleeding phenomena such as wound oozing are very common, and common hemostasis methods include compression hemostasis and electrocoagulation hemostasis. However, these conventional hemostasis methods are not always useful. For example, for larger wounds on the pelvic floor and abdominal cavity, long-term compression hemostasis and electrocoagulation hemostasis are not suitable. For wounds in the oral cavity, due to the particularity of the oral environment, the aforementioned conventional hemostasis methods also have some problems.
[0003] Patent No. CN113398317B records a hemostatic material and its preparation method, in which the decellularized animal tissue is digested and dried, and the hemostatic time of the material is regulated by controlling the PBS concentration in the digestion fluid; Patent No. CN116785493B provides a hollow composite double-layer nasal hemostatic sponge, a preparation method and its application, using EDC / NHS to cross-link the decellularized material - chitosan.
[0004] However, when hemostatic materials are used in practice, not only the hemostatic performance can be taken into consideration, but also other properties such as material mechanics. Summary of the invention
[0005] In order to overcome the above problems, a method is provided that can be used for timely and rapid hemostasis in surgical operations while ensuring the mechanical properties of the material, and can still continuously and effectively solve wound bleeding and bleeding in life scenarios after the completion of the surgical operation, prevent wound infection and inflammation, and also have a certain function of guiding tissue growth. The first aspect of the present invention proposes an application of a cross-linked natural biomatrix in the preparation of wound hemostasis and / or filling materials, especially wound hemostasis and / or filling materials in the field of pelvic floor, wound hemostasis and / or filling materials in the field of abdominal cavity, and wound hemostasis and / or filling materials in the field of oral implants. Wherein, the cross-linking degree of the cross-linked natural biomatrix is 31.71-75.98%, and the 4-hour volume swelling rate of the cross-linked natural biomatrix is 20-50%.
[0006] As a preferred embodiment, the degree of cross-linking of the cross-linked natural biological matrix is 31.71-75.98%, and the 4-hour volume swelling rate of the cross-linked natural biological matrix is 20-43%.
[0007] Preferably, the degree of cross-linking of the cross-linked natural biological matrix is 42.85-75.98%.
[0008] Preferably, the cross-linking index of the cross-linked natural biological matrix is 57.21-71.98%.
[0009] The second aspect of the present invention provides a method for preparing a cross-linked natural biological matrix, which is used for the application of the cross-linked natural biological matrix in preparing wound hemostasis and / or filling materials. The preparation method is as follows:
[0010] S1. Natural biological tissues are sterilized, defatted and decellularized and then crushed into powder;
[0011] S2. After the powder is extracted and purified, it is shaped and dried to obtain a prototype sponge;
[0012] S3. The prototype sponge is obtained after light treatment, cross-linking and freeze-drying.
[0013] As a preferred embodiment, in the step S1, the natural biological tissue is pulverized after being disinfected, defatted and decellularized, and then sieved through a 16-32 mesh sieve to obtain powder.
[0014] Preferably, in step S1, the diameter of the powder obtained by sieving through a 16-32 mesh sieve after pulverization is 500-1000 μm.
[0015] Preferably, the natural biological tissue is selected from any one of pig bladder, small intestinal submucosa, and dermis.
[0016] Preferably, step S1 is: the natural biological tissue is immersed in a 1-10wt% peracetic acid / 1-10wt% ethanol mixed disinfectant for 5-10 minutes for disinfection, then extracted with an organic solvent such as chloroform and anhydrous ethanol for defatting, and then, decellularized at room temperature using an enzymatic method, rinsed with pure water, dried, and ground into powder.
[0017] In step S1, the diameter of the powder will affect the performance of the final material obtained. Generally speaking, the physical form of the raw material before enzymolysis will not affect the product obtained after enzymolysis or the product processed after enzymolysis. However, the inventors found that in the present technical solution, the physical form of the raw material before extraction in step S2 has a certain influence on the degree of cross-linking of the final material obtained, that is, in step S1, the diameter of the powder will affect the degree of cross-linking of the final material obtained. This may be due to the combined effect of the influence of the extraction efficiency and the influence of the fluidity of the material during the extraction process. The crushing of the material in step S1 will first physically cut off the collagen in the material, and secondly, the change in specific surface area and fluidity caused by the size of the powder will change its contact area with the extract, which will further affect the chemical cutting of the collagen peptide chain during the extraction process, resulting in the length and molecular weight of the peptide chain being affected thereafter, thereby affecting the length and molecular weight of the purified and precipitated polypeptide again. This effect is more obvious when the number of extractions described in the present invention is 2 or 3 times and when a mixed electrolyte solution is used during purification.
[0018] As a preferred embodiment, in step S2, the extraction is performed by enzymatic hydrolysis using pepsin.
[0019] As a preferred embodiment, in step S2, the number of extractions is 2 or 3, the single extraction time is 2-48 hours, and the extraction time varies; in step S2, the pH environmental conditions are different during each extraction.
[0020] As a preferred implementation, in step S2, when the extraction time is 2 times, the first extraction time is greater than the second extraction time; when the extraction time is 3 times, the second extraction time is greater than the first extraction time and the third extraction time.
[0021] Preferably, in step S2, when the extraction time is 2 times, the first extraction time is 4-8h, the pH is 2-3, the pH is adjusted for the second extraction, the second extraction time is 3-4h, and the pH is 3.4-3.9; when the extraction time is 3 times, the first extraction time is 3-4h, the pH is 1.5-2, the pH is adjusted for the second extraction, the second extraction time is 8-24h, the pH is 3.1-4.2, the pH is adjusted for the third extraction, the third extraction time is 2-3h, and the pH is 3.4-3.9.
[0022] Preferably, during the extraction in step S2, the mass ratio of powder to pepsin is (50-500):(1-5).
[0023] As a preferred embodiment, the step S2 specifically comprises: after the powder is extracted, a viscous liquid is obtained, and the viscous liquid is transferred into an electrolyte solution for purification, the volume ratio of the viscous liquid to the electrolyte solution is (1-5): (1-5), the purification temperature is 2-9°C, after 10-24 hours, centrifugation is performed, the precipitate is taken, shaped, and dried to obtain a prototype sponge; the electrolyte solution is a mixture of a chloride aqueous solution with a concentration of 0.5-1.4 mol / L and a sulfate aqueous solution with a concentration of 4-12 mol / L, and in the electrolyte solution, the volume ratio of the chloride aqueous solution with a concentration of 0.5-1.4 mol / L and the sulfate aqueous solution with a concentration of 4-12 mol / L is (1-3): (0.1-1.2).
[0024] Chloride salt is sodium chloride or potassium chloride.
[0025] The sulfate is selected from at least one of ammonium sulfate, potassium sulfate and sodium sulfate.
[0026] As a preferred embodiment, in step S3, the sponge prototype is subjected to light treatment by immersing the sponge prototype in 0.14-0.78 mg / L riboflavin PBS buffer for 5-30 min and then irradiating with an irradiance of 2-6 mW·cm -2 , intermittent irradiation with ultraviolet light of wavelength 350-400nm for 15-45min.
[0027] Preferably, intermittent ultraviolet light irradiation is specifically as follows: after ultraviolet light irradiation for 15-45 minutes, the ultraviolet light is turned off and left for 15-45 minutes, and the above steps of ultraviolet light irradiation and turning off ultraviolet light are repeated 2-5 times in total.
[0028] As a preferred embodiment, in step S3, the prototype sponge is light-treated, cross-linked with an EDC / NHS mixture, and freeze-dried to obtain the sponge.
[0029] The CAS number of EDC is 1892-57-5, and the CAS number of NHS is 6066-82-6.
[0030] Preferably, in step S3, after the sponge prototype is treated with light, it is immersed in the EDC / NHS mixture for 12-36 hours for cross-linking. The relationship between the volume of the EDC / NHS mixture and the mass of the sponge prototype does not need to be specifically limited, as long as the EDC / NHS mixture can immerse the sponge prototype.
[0031] Preferably, in step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the concentration of EDC powder in 95wt% ethanol is 0.1-1wt%, and the concentration of NHS powder in 95wt% ethanol is 0.01-1wt%.
[0032] Preferably, in step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 0.1-1wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.01-0.5wt%.
[0033] Preferably, in step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 0.1-0.5wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.01-0.5wt%.
[0034] Preferably, in step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 0.1-0.3wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.01-0.2wt%.
[0035] Preferably, in step S3, after cross-linking, the mixture is rinsed with phosphate buffered saline (PBS), then rinsed with deionized water, and freeze-dried to obtain the product.
[0036] Beneficial Effects
[0037] (1) The cross-linked natural biomatrix of the present invention has good degradation performance while ensuring an appropriate degree of cross-linking and significantly improving mechanical properties such as tensile properties and Young's modulus relative to uncross-linked materials. When used as a filling material, such as a dental implant filling material, it can be degraded in time after fulfilling its hemostasis and tissue cell ingrowth functions, which is beneficial to the mechanical support of alloys and other metal or non-metal materials filled with dental implants, the chewing function of the implant, and the combination of the aforementioned materials and soft tissues.
[0038] (2) The material described in the present invention has a good ability to promote cell survival and is beneficial to accelerate wound recovery.
[0039] (3) Before EDC / NHS crosslinking, the prototype sponge was treated with intermittent light under specific conditions. Specifically, the prototype sponge was immersed in 0.14-0.78 mg / L riboflavin PBS buffer for 5-30 min and then treated with light at an irradiance of 2-6 mW·cm -2, intermittent irradiation with ultraviolet light of wavelength 350-400nm for 15-45min. Riboflavin-ultraviolet light pre-crosslinking can effectively control the degree of crosslinking of secondary crosslinking, and at the same time improve the volume swelling rate of the material. When applied to the wound surface, it reduces the risk of local soft tissue damage caused by squeezing the wound, which is beneficial to wound recovery. At the same time, although the volume swelling rate is reduced, the water absorption rate is not significantly reduced, thereby achieving a rapid hemostatic effect. This is particularly suitable for in vivo implant materials, especially for wound hemostasis and / or filling materials in the pelvic floor field that have relatively high requirements for degradation performance and self-hemostasis performance, wound hemostasis and / or filling materials in the abdominal cavity field, and wound hemostasis and / or filling materials in the field of oral dental implants.
[0040] (4) By controlling the diameter of the powder in step S1 and the specific multiple extractions in step S2, the subsequent light treatment and EDC / NHS cross-linking are further processed, so that the cross-linking degree of the obtained cross-linked natural biomatrix is in the range of 31.71-75.98%. At this time, the comprehensive performance of the material is suitable, with certain rigidity and toughness. While ensuring the mechanical properties of the material, it can not only be used for timely and rapid hemostasis in surgical operations, but also in life scenarios after the completion of the surgical operation, it can still continuously and effectively solve the wound bleeding and bleeding, prevent wound infection and inflammation, and also have a certain application of guiding tissue growth function. DETAILED DESCRIPTION
[0041] All materials used in the examples are commercially available. Pepsin was purchased from Sigma, catalog number P7125-100G.
[0042] Example 1
[0043] This example provides a method for preparing a cross-linked natural biological matrix, and the preparation method is as follows:
[0044] S1. Natural biological tissue (specifically, small intestinal submucosa, small intestinal submucosa tissue from pigs) is immersed in a 5wt% peracetic acid / 5wt% ethanol mixed disinfectant for 10 minutes for disinfection, then extracted with organic solvents such as chloroform and anhydrous ethanol for defatting, and then decellularized at room temperature using an enzymatic method (refer to the decellularization method described in Example 1 of Patent No. CN107007886B), rinsed with pure water, dried, ground and sieved through an 18-mesh sieve to obtain a powder.
[0045] S2. The powder is extracted twice (specifically, 0.5 g of the powder obtained in step S1 and 5 mg of pepsin are added to 100 mL of water, that is, the mass ratio of the powder to the pepsin is 100:1, and the pH is adjusted to 3 with an acetic acid aqueous solution for the first extraction. After 6 hours, deionized water is added to adjust the pH to 3.5 for the second extraction, and the second extraction time is 4 hours). After the powder is extracted, a viscous liquid is obtained, and the viscous liquid is transferred to an electrolyte solution for purification (the volume ratio of the viscous liquid to the electrolyte solution is 1:1). The purification temperature is 5°C. After 14 hours, centrifugation is performed, and the precipitate is taken, placed in a mold for shaping, and dried at 35°C for 24 hours to obtain a prototype sponge; the electrolyte solution is a mixture of a sodium chloride aqueous solution with a concentration of 0.8 mol / L and an ammonium sulfate aqueous solution with a concentration of 7 mol / L. In the electrolyte solution, the volume ratio of the sodium chloride aqueous solution with a concentration of 0.8 mol / L and the ammonium sulfate aqueous solution with a concentration of 7 mol / L is 1.9:0.6.
[0046] S3. The prototype sponge was treated with light (specifically, the prototype sponge was immersed in 0.26 mg / L riboflavin PBS buffer for 15 min and then treated with an irradiance of 5 mW·cm -2 , intermittent irradiation with ultraviolet light of wavelength 350nm, that is, after ultraviolet light irradiation for 25min, turn off the ultraviolet lamp and leave it for 15min, repeat the above steps of ultraviolet light irradiation and turning off ultraviolet light for a total of 3 times), then put it into EDC / NHS mixture for cross-linking so that the EDC / NHS mixture can immerse the prototype sponge, soak for 24h; after cross-linking, rinse with phosphate buffered saline (PBS) 3 times, rinse with deionized water 4 times, and freeze-dry to obtain.
[0047] In step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 0.3wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.1wt%.
[0048] Example 2
[0049] This example provides a method for preparing a cross-linked natural biological matrix, which is different from Example 1 in that step S2. The powder is extracted three times (specifically, 0.5 g of the powder obtained in step S1 and 5 mg of pepsin are added to 100 mL of water, the mass ratio of powder to pepsin is 100:1, the pH is adjusted to 2 with an acetic acid aqueous solution, and the first extraction is performed. After 3 hours, deionized water is added to adjust the pH to 4.2 for the second extraction, and the second extraction time is 12 hours; the pH is adjusted to 3.6 with an acetic acid aqueous solution, and the third extraction is performed, and the extraction time is 2 hours), after purification, it is placed in a mold for shaping, and dried at 35° C. for 24 hours to obtain a prototype sponge.
[0050] In step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 1wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.4wt%.
[0051] Example 3
[0052] This example provides a method for preparing a cross-linked natural biological matrix, which is different from Example 2 in that, in step S2, the powder is extracted three times (specifically, 0.5 g of the powder obtained in step S1 and 10 mg of pepsin are added to 100 mL of water, the mass ratio of powder to pepsin is 50:1, the pH is adjusted to 2 with an acetic acid aqueous solution, the first extraction is performed, 3 hours later, deionized water is added to adjust the pH to 4.2 for the second extraction, the second extraction time is 8 hours; the pH is adjusted to 3.6 with an acetic acid aqueous solution, the third extraction is performed, and the extraction time is 2 hours), after purification, it is placed in a mold for shaping, and dried at 35° C. for 24 hours to obtain a prototype sponge.
[0053] In step S3, the EDC / NHS mixture is prepared by adding EDC powder and NHS powder to 95wt% ethanol, so that the weight ratio of EDC powder in 95wt% ethanol is 0.5wt%, and the weight ratio of NHS powder in 95wt% ethanol is 0.3wt%.
[0054] Example 4
[0055] This example provides a method for preparing a cross-linked natural biological matrix. Different from Example 1, the prototype sponge in S3 is subjected to light treatment, specifically, the prototype sponge is immersed in 0.26 mg / L riboflavin PBS buffer for 15 min and then treated with an irradiance of 5 mW·cm -2 , 350nm wavelength ultraviolet light was irradiated for 45min.
[0056] Comparative Example 1
[0057] This example provides a method for preparing a cross-linked natural biomatrix. The difference from Example 1 is that in step S1, the powder is ground and crushed and then screened through a 5-mesh sieve to obtain a powder with a particle size of 4 mm. In step S2, the powder only needs to be extracted once (specifically, 0.5 g of the powder obtained in step S1 and 5 mg of pepsin are added to 100 mL of water, the mass ratio of powder to pepsin is 100:1, the pH is adjusted to 3.5 with acetic acid aqueous solution, and the extraction time is 10 hours).
[0058] Comparative Example 2
[0059] This example provides a method for preparing a cross-linked natural biological matrix. The difference from Example 1 is that in step S2, the powder is extracted three times (specifically, 0.5 g of the powder obtained in step S1 and 5 mg of pepsin are added to 100 mL of water, the mass ratio of powder to pepsin is 100:1, the pH is adjusted to 2 with an acetic acid aqueous solution, and the first extraction is performed. After 5 hours, deionized water is added to adjust the pH to 4.2 for the second extraction, and the second extraction time is 5 hours; the pH is adjusted to 3.6 with an acetic acid aqueous solution, and the third extraction is performed, and the extraction time is 5 hours), after purification, it is placed in a mold for shaping, and dried at 35° C. for 24 hours to obtain a prototype sponge.
[0060] Comparative Example 3
[0061] This example provides a method for preparing a cross-linked natural biological matrix. The difference from Example 1 is that in step S2, after the powder is extracted, a viscous liquid is obtained, and the viscous liquid is transferred into an electrolyte solution for purification (the volume ratio of the viscous liquid to the electrolyte solution is 1:1). The purification temperature is 5°C. After 14 hours, centrifugation is performed, and the precipitate is taken, placed in a mold for shaping, and dried at 35°C for 24 hours to obtain a prototype sponge; the electrolyte solution is a sodium chloride aqueous solution with a concentration of 0.8 mol / L.
[0062] Comparative Example 4
[0063] This example provides a method for preparing a cross-linked natural biological matrix. The difference from Example 1 is that in step S3, the prototype sponge is not subjected to light treatment but is directly placed in the EDC / NHS mixture for cross-linking.
[0064] Comparative Example 5
[0065] This example provides a method for preparing a degradable cross-linked natural biological matrix. The difference from Example 1 is that in step S3, the method for preparing the EDC / NHS mixture is to add EDC powder and NHS powder to 95wt% ethanol, so that the concentration of EDC powder in 95wt% ethanol is 2wt%, and the concentration of NHS powder in 95wt% ethanol is 1wt%.
[0066] Performance Test:
[0067] 1. Cross-linking degree test: The cross-linking degree of the samples obtained in Examples 1-4 and Comparative Examples 1-5 was determined by the reduced ninhydrin method, and the N0 group represented the free α-amino acid content in the uncross-linked sample (the control example, the preparation method of the control example was steps S1 and S2 in the corresponding example, that is, the prototype sponge obtained in the corresponding example was the control example sample of the degradable cross-linked natural biological matrix sample obtained in each example in the cross-linking degree test), and N x The group represents the α-amino acid content in each group of samples. The cross-linking degree of each group of materials is calculated according to the following formula: CI = (N0-N x) / N0×100%, the results are shown in Table 1:
[0068] Table 1
[0069] Example Degree of cross-linking (%) Example 1 75.98 Example 2 57.21 Example 3 31.71 Example 4 42.85 Comparative Example 1 92.53 Comparative Example 2 98.65 Comparative Example 3 65.72 Comparative Example 4 27.62 Comparative Example 5 75.32
[0070] Although cross-linking can improve the properties of materials, such as the higher the degree of cross-linking, the greater the rigidity of the material and the less likely it is to deform, a high degree of cross-linking also means that it is less likely to degrade. In addition, as an implant device, the higher the degree of cross-linking, the more likely the human body will have adverse reactions such as allergies and redness. Therefore, it is not the case that the higher the degree of cross-linking, the better. The cross-linking degree of the cross-linked natural biomatrix obtained by the present invention is controlled within 75.98%, especially the cross-linking degree range of 31.71-75.98%, and the comprehensive performance of the material is suitable.
[0071] 2. Water absorption test: Weigh the samples of Examples 1-4 and Comparative Examples 1-5 (record the initial mass of the samples M0, the initial volume of the samples V0) and add them to deionized water (record the mass of the deionized water at this time M1), immerse the samples in deionized water, take them out at 4h and 12h respectively, record the mass of the remaining water M2 after taking them out, and measure the volume V of the samples at this time after absorbing the excess water on the surface of the samples with filter paper. The volume swelling rate is calculated according to the formula (V-V0) / V0×100%, and the water absorption rate is calculated according to the formula (M1-M2) / M0×100%. The results are shown in Table 2:
[0072] Table 2
[0073]
[0074] It can be seen from Example 1 and Comparative Example 4 that, compared with Comparative Example 4, Example 1 using the specific light treatment step of the present invention has a significantly reduced volume swelling rate of the sample of Example 1, but the water absorption rate is not significantly reduced; it can also be seen from Example 1 and Comparative Example 5 that, compared with Comparative Example 5, Example 1 further controls the EDC / NHS ratio (that is, when preparing the EDC / NHS mixture, the concentration of the EDC powder in 95wt% ethanol is controlled to be 0.1-1wt%, and the concentration of the NHS powder in 95wt% ethanol is controlled to be 0.01-1wt%), and the sample of Example 1 shows a smaller volume swelling rate within 4 hours. At the same time, it can be seen from Table 3 that the sample of Example 1 can achieve relatively good coagulation performance.
[0075] 3. Coagulation index test: Weigh 0.1 g of the samples obtained in Examples 1-4 and Comparative Examples 1-5 respectively and place them in a beaker, take 1 mL of fresh blood and drop it on the sample, and then add 0.2 mL of saturated CaCl2 aqueous solution, add 250 mL of deionized water after 5 minutes and mix well, and measure the absorbance value A1 at a wavelength of 415 nm; set the blank control substance added with the material of the present invention to test the absorbance value A0, and calculate the coagulation index according to the formula A1 / A0×100%. The smaller the coagulation index, the better the hemostatic effect. The results are shown in Table 3:
[0076] Table 3
[0077] Example Coagulation index (%) Example 1 10.4 Example 2 13.2 Example 3 13.9 Example 4 12.8 Comparative Example 1 21.5 Comparative Example 2 20.3 Comparative Example 3 14.1 Comparative Example 4 36.5 Comparative Example 5 19.3
[0078] 4. Mechanical properties test: The elastic modulus and tensile strength of the samples obtained in Examples 1-4 and Comparative Examples 1-5 were tested using a multifunctional biomechanical testing machine. The higher the elastic modulus, the stronger the ability of the material to resist elastic deformation when subjected to force. The results are shown in Table 4:
[0079] Table 4
[0080] Example <![CDATA[Modulus of elasticity (N / mm 2 ).]]> Tensile strength (MPa) Example 1 17.28 5.51 Example 2 13.43 3.87 Example 3 7.08 3.15 Example 4 7.55 3.32 Comparative Example 1 19.36 4.61 Comparative Example 2 18.75 4.08 Comparative Example 3 11.25 3.56 Comparative Example 4 4.26 1.06 Comparative Example 5 14.58 4.82
[0081] 5. Cell viability test: The materials were cut into 1 cm × 1 cm pieces and fixed to the bottom of a culture dish. NIH3T3 cells were used as model cells and cultured at 37°C and 5% CO2 for 72 h. The cell viability of the materials obtained in Examples 1-4 and Comparative Examples 1-5 was determined by the MTT method according to GB / T 16886.5-2003. The results are shown in Table 5.
[0082] Table 5
[0083] Example Cell survival rate (%) Example 1 117.4 Example 2 113.2 Example 3 108.3 Example 4 111.5 Comparative Example 1 79.8 Comparative Example 2 69.2 Comparative Example 3 51.4 Comparative Example 4 105.2 Comparative Example 5 71.8
[0084] 6. In vitro degradation test: The samples obtained in Example 1, Example 4 and Comparative Examples 1-2 and Comparative Example 4 were cut into cylinders with a bottom diameter of 1 cm and a height of 5 mm, weighed (m) and placed in 20 mL of 1-5 U / mL collagenase (GIBCO TM , Product No. PM11573) aqueous solution, sealed, placed in a 37°C shaker, took out the samples from the shaker at 1 week, 2 weeks, and 3 weeks, soaked in water for 30 min, transferred to 95wt% ethanol aqueous solution and soaked for 30 min, and finally vacuum dried at 60°C for 24 h to dehydrate, and weighed (m n ), degradation rate (mm n ) / m×100%, the results are shown in Table 6:
[0085] Table 6
[0086]
[0087] In summary, the samples of Examples 1-4 all have good comprehensive properties.
[0088] Although the degree of crosslinking of Example 3-4 is slightly lower than that of Example 1-2, the degradation performance is more suitable. At the same time, other properties such as water absorption, volume swelling rate, coagulation index, cell survival rate, etc. are good, so it also has good application prospects, but the elastic modulus is slightly lower than that of Example 1 and Example 2, and it is softer. Therefore, relative to the materials obtained in Examples 1 and 2, the materials obtained in Examples 3-4 are more suitable for use in larger wound scenes such as the abdominal cavity and pelvic floor, while the materials obtained in Examples 1 and 2 are more suitable for use in oral scenes. Although Comparative Example 5 increases the concentration of the EDC / NHS crosslinker, it does not significantly increase its degree of crosslinking, indicating that riboflavin-UV pre-crosslinking can effectively control the crosslinking results.
[0089] The crosslinking degree of the material obtained in Comparative Examples 1-2 is too high. Theoretically, too high a degree of crosslinking may cause the material to become rigid, which is not conducive to cell infiltration. At the same time, the degradation performance will also decrease to a certain extent, which may cause inflammation, thereby affecting the effect of cell ingrowth. In the test of cell survival rate, its trend can also be seen. The materials obtained in Comparative Examples 1-2 are all lower than 100% in the cell survival rate experiment, indicating that they may not be able to promote cell proliferation very well. The long degradation time of the material obtained in Comparative Example 2 in the degradation experiment is also consistent with the above view.
Claims
1. An application of a cross-linked natural biological matrix in the preparation of wound hemostasis and / or filling materials, characterized in that: in, The degree of cross-linking of the cross-linked natural biological matrix is 31.71-75.98%, and the 4-hour volume swelling rate of the cross-linked natural biological matrix is 20-50%. The preparation method of the cross-linked natural biological matrix is as follows: S1. Natural biological tissues are sterilized, defatted and decellularized and then crushed into powder; S2. After the powder is extracted and purified, it is shaped and dried to obtain a prototype sponge; S3. The prototype sponge is obtained after light treatment, cross-linking and freeze-drying.
2. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: The 4-hour volume swelling ratio of the cross-linked natural biomatrix was 20-43%.
3. Use of the cross-linked natural biological matrix according to claim 1 or 2 in preparing wound hemostasis and / or filling materials, characterized in that: The wound hemostasis and / or filling material includes wound hemostasis and / or filling material in the pelvic floor field, wound hemostasis and / or filling material in the abdominal cavity field, and wound hemostasis and / or filling material in the oral dental implant field.
4. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: In the step S1, the natural biological tissue is pulverized after being disinfected, defatted and decellularized, and then sieved through a 16-32 mesh sieve to obtain powder.
5. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: In the step S2, the number of extractions is 2 or 3, the single extraction time is 2-48 hours, and the extraction time is different each time; in the step S2, the pH environmental conditions are different during each extraction.
6. The use of the cross-linked natural biological matrix according to claim 5 in preparing wound hemostasis and / or filling materials, characterized in that: In step S2, when the extraction time is 2 times, the first extraction time is greater than the second extraction time; when the extraction time is 3 times, the second extraction time is greater than the first extraction time and the third extraction time.
7. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: Specifically, step S2 comprises extracting the powder to obtain a viscous liquid, transferring the viscous liquid into an electrolyte solution for purification at a temperature of 2-9° C. for 10-24 hours, centrifuging, taking the precipitate, shaping, and drying to obtain a prototype sponge; The electrolyte solution is a mixture of a chloride aqueous solution with a concentration of 0.5-1.4 mol / L and a sulfate aqueous solution with a concentration of 4-12 mol / L. In the electrolyte solution, the volume ratio of the chloride aqueous solution with a concentration of 0.5-1.4 mol / L and the sulfate aqueous solution with a concentration of 4-12 mol / L is (1-3): (0.1-1.2).
8. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: In step S3, the sponge prototype is subjected to light treatment by immersing the sponge prototype in a 0.14-0.78 mg / L riboflavin PBS buffer for 5-30 min and then irradiating the sponge prototype with an irradiance of 2-6 mW·cm -2 , intermittent irradiation with ultraviolet light of wavelength 350-400nm for 15-45min.
9. The use of the cross-linked natural biological matrix according to claim 1 in preparing wound hemostasis and / or filling materials, characterized in that: In the step S3, the prototype sponge is treated with light, cross-linked with an EDC / NHS mixture, and freeze-dried to obtain a sponge.
Citation Information
Patent Citations
A biological tissue matrix material, its preparation method and its uses
CN107007886B
A hemostatic material and its preparation method
CN113398317B
Collagen hydrogel as well as preparation method and application thereof
CN116510070A